Суверенітет як обов’язок: нове розуміння концепту - Нігреєва, О.О. (Альманах права, 2012)
У статті авторка торкається питань трансформації поняття суверенітету в сучасних умовах. Починаючи із розгляду класичної теорії суверенітету, яку протягом довгого часу визнавали чи не єдино можливою, дослідниця звертається до однієї з останніх його концепцій — концепції «суверенітету, що зобов’язує», аргументуючи закономірність її появи. В статье автор затрагивает вопросы трансформации понятия суверенитета в современных условиях. Начиная с рассмотрения классической теории суверенитета, которая долгое время признавалась, чуть ли не единственно возможной, исследователь обращается к одной из последних его концепций — концепции «обязывающего суверенитета», аргументируя закономерность ее появления. In the article the author touches some issues of sovereignty concept transformation in the modern conditions. Beginning with consideration of the classic sovereignty theory that during a long period of time was recognized as an almost unique possibility, the researcher turns to one of its recent conceptions to the conception of «sovereignty
as responsibility», proving regularity of its appearance. For years sovereignty was one of the most important characteristics of a state that was making it legally independent and free from influence of other international law subjects. Nowadays realities want the classic sovereignty conception to be changed as far as it prevents from
solving of some important international tasks. One of such tasks is the human rights defense. At the end of the 20th century the mankind became a witness of the great tragedies that had place in the former Yugoslavia, Ruanda and others places of the world. One of the main reasons of genocide crimes in these countries was impossibility
of the international society to intervene in the events as they were realized in territories of the sovereign states. So the quality of sovereignty became an obstacle to prevention of such serious and grave international crime as the genocide crimes. In these conditions the sovereignty is connected with questions of international law, such as: when,
if ever, is intervention by one country or several countries or an international organization onto another’s territory permissible? Inaction in response to the Rwanda genocide in 1994 and failure to halt the 1995 Srebrenica massacre in Bosnia highlight the complexities of international responses to crimes against humanity. In 2000, the Canadian government and several other actors announced the establishment of the International Commission on Intervention and State Sovereignty to address the challenge of the international community’s responsibility to act in the face of
the gravest of human rights violations while respecting the sovereignty of states. It sought to bridge these two concepts with the 2001 Responsibility to Protect report. In 2005 the responsibility to protect doctrine was incorporated into the World Summit outcome document. The document did say it was every state’s responsibility to protect its citizens from genocide, war crimes, ethnic cleansing, and crimes against humanity. If a state fails to do so, it then becomes the responsibility of the international community to protect that state’s population in accordance with Chapter VII of the UN Charter. Chapter VII includes use of military force by the international community if peaceful measures
prove inadequate. The UN outcome document was unanimously adopted by all member states though is not legally binding. Such an approach of the international community to the intervention possibility means a serious change of the classical sovereignty conception that may conduct to changes in the conception of state itself. Some author’s thoughts that concern to these changes are exposed in the article.